Modeling and Application of Pedestrian Safety Conflict Index at Signalized Intersections. (31st March 2014) - Cheng, Wei; Zhang, Ning; Li, Wei; Xi, Jianfeng
Abstract : Traffic conflict between turning vehicles and pedestrians is the leading cause of pedestrian fatalities at signalized intersections. In order to provide a solution for evaluating intersection safety for vulnerable road users, this paper first determines the most important factors in analyzing pedestrian-vehicle conflict and puts forward a pedestrian safety conflict index (SCI) model to establish a quantitative standard for safety evaluation of two- or multiphase intersections. A safety level system is then designed based on SCI to help categorize and describe the safety condition of intersections applicable to the model. Finally, the SCI model is applied to the evaluation of two intersections in the city of Changchun, the result of which complies with expectation, indicating the model's potential in providing an improved approach for pedestrian-vehicle conflict evaluation study.